Análise da resistência ao bicho-mineiro e caracterização de genótipos de Coffea arabica com microssatélites - Pereira, Gabriella Santos (2011)
In breeding programs of research institutions of coffee in Brazil seek to genotype Coffea arabica resistant to leaf miner, a pest that causes major damage to coffee crops. Molecular markers of microsatellite or SSR may be an alternative in plant breeding programs, accelerating the development of new genotypes with resistance to this pest. These markers can also be used for the characterization of cultivars in germplasm banks. The objective of this research, analyze genotypes of Coffea arabica segregating for the trait of resistance to leaf miner and to characterize genotypes of arabica coffee, using molecular markers SSR and EST-SSR. For the analysis of resistance to leaf miner were used 66 loci SSR (simple sequence repeat), of which 63 were developed from EST (expression sequence tag) Genome Café These primers were tested in bulks of resistant individuals from 10 families and 10 susceptible families and eight accessions of Coffea racemosa, characteristic of the donor species for resistance to leaf miner. It was observed polymorphism between resistant and susceptible genotypes when using two primers. Next, we analyzed 78 individuals from 10 families susceptible and resistant 55 of 10 families and 37 individuals in F5 resistant and 54 susceptible F6. The two polymorphic alleles identified by the two primers were present in approximately 70% of susceptible genotypes in F5 and in approximately 90% of susceptible individuals in F6. We found no allele linked to the resistance trait under study. It was possible to distinguish genotypes of arabica coffee resistant to leaf miner in relation to susceptible by microsatellite markers. To characterize the genotypes, 38 primers were used, 34 EST-SSR type in 12 cultivars and three clones of C. arabica. Seven polymorphic loci were observed among genotypes. For dendrogram from Jaccard coefficients, we observed a lower genetic similarity values, 0.88, and between cultivar Acauã the other genotypes and similarity of 100% for seven cultivars and one clone. It was possible to characterize the cultivars Acauã, IBC-2 Palm, and Sabia Late Icatu Amarelo IAC 3282 by seven primers.